Phenetic analysis of the complex Senna fabrisii—S. trichosepala (Leguminosae, Caesalpiniodeae, Aphyllae) based on morphological characters and seed protein electrophoretic profiles - Robbiati, Federico O.; Lamarque, Alícia; Anton, Ana M.; Fortunato, Renée H. (Phytotaxa, 2013)
Multivariate and univariate analyses based on morphological characters and seed soluble protein electrophoretic profiles were carried out in order to understand the taxonomic status within the complex S. fabrisii-S. trichosepala. Twenty morphological characters from herbarium specimens were recorded and analyzed by ANOVA, principal component and cluster analysis. The seed protein electrophoretic analysis including cluster analysis was based on three populations: one of S. fabrisii and two of S. trichosepala. The results showed that both taxa differed only by three morphological features; in parallel, the CPA and CA demonstrate that no clearly separated group can be recognized. The seed protein electrophoretic profiles show a high degree of similarity. Based on these results, and due to the variability observed, the inclusion of S. fabrisii in the synonymy of S. trichosepala is proposed.